(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
The density in the working chamber increases due to the fact that raw cotton unevenly enters the saw gin feeders. To prevent this, our scientists have effectively carried out experiments and tests based on various proposals. The article provides details of a study conducted by scientists of our republic.